Effect of Green Finance, Zakat Performance Ratio, and Good Corporate Governance on SDGs in Islamic Commercial Banks - Novita Lela Sari; Any Eliza; Rahmat Fajar Ramdani (Department of Islamic Banking, 2025)
Purpose – This study aims to examine the impact of Green Finance, the Zakat Performance Ratio, and Good Corporate Governance on the achievement of Sustainable Development Goals in Indonesian Islamic commercial banks. Methodology – The type of research employed in this study is quantitative research, as it is based on positivism for data collection and analysis, to test hypotheses. Samples in this study were obtained using purposive sampling. The criteria considered are Islamic banks that issue annual reports and Sustainability reports, as well as the issuance of zakat distribution reports. Based on the determination of these categories, 14 Islamic banks were selected as the sample of this study. Findings – Based on the study’s results, it was concluded that Green Finance has an impact on the Sustainable Development Goals, whereas Zakah Performance Ratio and Good Corporate Governance do not. Simultaneously, Green Finance, Zakat Performance Ratio, and Good Corporate Governance affect the Sustainable Development Goals. Implications – This study may serve as a valuable guide for developing more sustainable business plans, regulations, and operational procedures, enabling Indonesia’s Islamic banking industry to contribute more effectively to achieving the Sustainable Development Goals. Originality – This study offers originality by simultaneously integrating Green Finance, Zakat Performance Ratio, and Good Corporate Governance as key variables that have not been studied together in the unique context of Islamic commercial banks in Indonesia, to measure their contribution to achieving the Sustainable Development Goals.